ИМКАНИЯТЫ ШЕКЛЕНГЕН БАЛАЛАР МЕНЕН ПСИХОКОРРЕКЦИЯЛЫҚ ЖУМЫСЛАРДЫ ШӨЛКЕМЛЕСТИРИЎ - Шеримбетова, З.Ш. (ILIM hám JÁMIYET, 2017)
The article deals with the study of psychological types of children with restricted abilities, the analysis of their individual – psychological peculiarities. The author gives the brief analysis of this issue done by the scientists-psychologists. She describes the correction works and gives recommendations to schools teachers.
Keywords: психология; психокоррекция; арттерапия; эмоция; гигиена; элементар предметли ҳаракатлар; фаолият